Validating patient and physician versions of the shared decision making questionnaire in oncology setting - Babak Nejati; Chien-Chin Lin; Vida Imani; Maria Browall; Chung-Ying Lin; Anders Broström; Amir H Pakpour (Tabriz University of Medical Sciences, 2019)
Background: This study investigated the psychometric properties of the 9-Item Shared DecisionMaking Questionnaire (SDM-Q-9) and the 9-Item Shared Decision-Making Questionnaire-Physician version (SDM-Q-Doc) using comprehensive and thorough psychometric methods in an oncology setting. Methods: Cancer survivors (n=1783; 928 [52.05%] males) and physicians (n=154; 121[78.58%] males) participated in this study. Each cancer survivor completed the SDM-Q-9. Physicians completed the SDM-Q-Doc for each of their cancer patient. Confirmatory factor analysis (CFA) and Rasch model were used to test the psychometric properties of SDM-Q-9 and SDM-Q-Doc. Results: SDM-Q-9 and SDM-Q-Doc demonstrated unidimensional structure in CFA and Rasch model. In addition, the measurement invariance was supported for both SDM-Q-9 and SDM-QDoc across sex using the multigroup CFA. Rash analysis indicates no differential item functioning(DIF)across sex for all the SDM-Q-9 and SDM-Q-Doc items. SDM-Q-9 and SDM-Q-Doc were moderately correlated (r=0.41; P<0.001). Conclusion: SDM-Q-9 and SDM-Q-Doc are valid instruments to assess shared decision making in the oncology setting.